Syndrome specific modules to enhance the Stepping Stones Triple P public health intervention. Issue 9 (September 2017) - Bezzina, L. A.; Rice, L. J.; Howlin, P.; Tonge, B. J.; Einfeld, S. L.
Abstract: Background: Service responses to behaviour phenotypes include care by expert clinicians, syndrome‐specific clinics, disability‐specific mental health services and generic mental health services. While these services contribute to care, they are often of limited accessibility. Methods: We describe a population‐wide public health intervention aimed at increasing the accessibility of services to the target population. Stepping Stones Triple P (SSTP) is a public health intervention of known efficacy in reducing behaviour problems when delivered to parents of children aged 0–12 with mixed developmental disabilities. Results: The strategy we discuss involves enhancing SSTP with modules for specific causes of developmental disabilities including Down, Fetal Alcohol, Fragile X, Prader–Willi and Williams syndromes. Conclusions: We propose that enhancing SSTP with syndrome specific modules will increase the accessibility of support to families who have a child with a specific behaviour phenotype. We suggest that future research should confirm the public health impact of the modified SSTP programme using the RE‐AIM framework.